SCIENTIFIC CREATIVITY PROJECT-BASED LEARNING FOR TECHNOLOGY-ORIENTED LEARNING: A VALIDITY AND PRACTICALITY ANALYSIS - Dimas Arya Soeadyfa Fridyatama; Muhammad Roil Billad; Farid Baskoro; Wahyu Sasongko Putro; Delmio Ave Mara Gutteres de Sousa (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2026)
Rapid technological transformation requires educational institutions to develop students’ scientific creativity, collaborative problem-solving, responsibility, and reflective reasoning skills in authentic learning environments. However, many students still experience difficulties in connecting scientific knowledge with real-world problem-solving and creative inquiry activities. This study aimed to evaluate the validity and practicality of the Scientific Creativity Project-Based Learning (SCPjBL) model as an instructional approach that integrates scientific creativity, collaborative inquiry, and character-oriented learning. The study employed research and development methodology involving 180 undergraduate students from two higher education institutions in Indonesia. Data were collected using validation sheets, observation instruments, questionnaires, and scientific creativity assessments. Three expert validators and four classroom observers participated in the evaluation process. The findings showed that the SCPjBL model achieved high validity, reliability, and practicality. The model obtained a validity percentage of 98.00%, while supporting learning tools and response questionnaires achieved 97.00% and 99.00%, respectively. Reliability analysis also demonstrated strong consistency with Cronbach’s Alpha of 0.85. Classroom observations indicated that the SCPjBL model effectively supported collaborative learning, scientific reasoning, reflective inquiry, and responsible project engagement. The findings suggest that SCPjBL can support scientific creativity, problem-solving, and character-oriented learning through authentic project-based educational activities.